An Analysis of Structural Resurrection of Words based on Layered Stylistics in the Syntax layer of the Contemporary Ghazal of Iran - Fariba Mehri; Mehyar Alavi Moghaddam; Hasan Delbri; Abbas Mohammadian (مطالعات زبانی و بلاغی)
In contemporary Ghazal, in order to defamiliarization and creatation of linguistic capacities, various approaches are used in the framework of norm-setting. In addition to enhancing the literary aspects of the speech, these approaches have become such a feature of style. The purpose of this article is to study the normative hypothesis of the syntax layer of contemporary ghazal based on layered stylistics. The fundamental question of the article is that the normative hypotheses of the syntax, in what parts of the chain of words occur in the most part, and what the poets would use for this purpose. On this base, after a brief introduction to linguistic stylistics and hijacking in the syntax of speech, authors introduce examples of this application, and in the end it is concluded that the hijacking of contemporary ghazal, both in the morphology and in the syntax, has influenced the word. Most of the cases are related to spontaneity, especially in the infinitive and verb areas, the construction of words and the use of exquisite attributes, and in the syntagmatic of speech, to be payed attention to normality of the syntactic layer.